Every one counts : examining Aboriginal youth incarceration by gender, statistics and Witsuwit'en laws - Whonnock, Karen (2018)
This dissertation examines the incarceration rates of Aboriginal youth in Canada as well as Witsuwit’en legal tradition regarding youth discipline. I explore Aboriginal youth incarceration rates, and examine regional differences and gender differences as well as obtain rich primary data from acknowledged Witsuwit’en knowledge keepers. Despite the abundance of materials on the over-incarceration rates of Aboriginal adult offenders, as documented in R. v. Gladue and R. v. Ipeelee, there is very little academic attention regarding over-incarceration rates of Aboriginal youth. However, the existing literature does point to the fact that the numbers of youth have dropped since the introduction of the Youth Criminal Justice Act (“YCJA”) but the Aboriginal youth rates are not dropping proportionately. There is an increasing over-representation of Aboriginal males, yet Aboriginal females in particular are worse off than other youth. Although this dissertation is not focussed primarily on the causation of Aboriginal youth detention, the secondary sources indicate a number of underlying reasons such as systemic discrimination, socio-economic factors, mental health and residential school impacts. The literature review indicates that Aboriginal youth over-incarceration is going to worsen over time. I have used an Indigenous methodology in my research which explores how Indigenous communities can develop, control and own the research. The Indigenous Legal Research Unit (“ILRU”) Method developed at the University of Victoria’s law school employs a case briefing model to examine the facts, issues, decisions and reasoning from Indigenous stories to develop an Indigenous legal framework. This ILRU method shows how Witsuwit’en stories were analyzed using the ILRU method. I also explore the reasons why statistics are in fact Indigenous. I compare and contrast the numbers of Aboriginal youth who are incarcerated across Canada by gender and Aboriginal status. This research employs a mixed methods approach drawing both from ...